The association between secondhand smoke and childhood asthma: A systematic review and meta‐analysis - He, Zonglin; Wu, Huailiang; Zhang, Siyu; Lin, Yuchen; Li, Rui; Xie, Lijie; Li, Zibo; Sun, Weiwei; Huang, Xinyu; Zhang, Casper J. P.; Ming, Wai‐kit (Pediatric pulmonology, 2020)
Background Secondhand smoke (SHS) exposure can trigger asthma exacerbations in children. Different studies have linked increased asthma symptoms and even deaths in children with SHS, but the risk has not been quantified uniformly across studies. We aimed to investigate the role of SHS exposure as a risk factor of asthma among children. Methods We performed a systematic review in PubMed, Scopus, and Google Scholar from June 1975 to 10 March 2020. We included cohort, case‐control, and cross‐sectional studies reporting odds ratio (OR) or relative risk estimates and confidence intervals of all types of SHS exposure and childhood asthma. Results Of the 26 970 studies identified, we included 93 eligible studies (42 cross‐sectional, 41 cohort, and 10 case‐control) in the meta‐analysis. There were significantly positive associations between SHS exposure and doctor‐diagnosed asthma (OR = 1.24; 95% confidence interval (CI) = 1.20‐1.28), wheezing (OR = 1.27; 95% CI = 1.23‐1.32) and asthma‐like syndrome (OR = 1.34; 95% CI = 1.34‐1.64). The funnel plots of all three outcomes skewed to the right, indicating that the studies generally favor a positive association of the disease with tobacco exposure. Subgroup analysis demonstrated that younger children tended to suffer more from developing doctor‐diagnosed asthma, but older children (adolescents) suffered more from wheezing. There was no evidence of significant publication or small study bias using Egger's and Begg's tests. Conclusion The results show a positive association between prenatal and postnatal secondhand smoking exposure and the occurrence of childhood asthma, asthma‐like syndrome, and wheezing. These results lend support to continued efforts to reduce childhood exposure to secondhand smoke.